Mulheres camponesas e o direito à aposentadoria rural: perspectivas acerca do tempo de serviço no campo e o acesso a benefícios previdenciários - Bringel, Fernanda Cristina Macedo (2025)
This dissertation has as its central theme the investigation into rural retirement age, focusing on the female figure in the agrarian context. The research seeks to understand the difficulties faced by peasant women in obtaining recognition of their social security rights. Taking into account invisibility, the sexual division of labor and bureaucratic and social barriers, this work explores how these women deal with proving the working time required by the INSS. The historical analysis of women's work in the field reveals ongoing oppression and the struggle for visibility and recognition, highlighting persistent gender inequality. Furthermore, the dissertation examines the social movements that articulate feminist struggles in the countryside and their contributions to gaining rights and improving living conditions. Finally, the challenges faced by rural women in proving their working time are discussed, highlighting the devaluation of their work and the difficulties imposed by social security, which often ignores the inequalities faced by these women. Regarding the method, a qualitative approach was used, with analysis of dissertations, theses, scientific articles, data from the INSS and the Federal Court, seeking to understand the complexity of the social security issues faced by peasant women and propose solutions that can contribute to the implementation of Your rights. At the end of the study, it is concluded that it is essential for the INSS and the Judiciary to adopt a gender-sensitive perspective, recognizing the specificities of women's work in rural areas and making the evidentiary requirements more flexible in order to ensure that rural women workers can access the right to retirement. The research highlights the importance of inclusive public policies and the strengthening of rural social organizations as key mechanisms to promote social security justice and gender equity in rural settings.